Evaluation of eruption of deciduous teeth among infants born after low risk pregnancy compared to infants diagnosed with Intra Uterine Growth Restriction - Aditi Garg; Gyanendra Kumar; Mridula Goswami; Devender Kumar; Devendra Mishra (Journal of Oral Biology and Craniofacial Research)
Purpose: The impact of IUGR on holistic growth of an infant is established however, limited evidence has been reported regarding its implication on eruption of deciduous dentition. Aim: Comparative evaluation of eruption of deciduous teeth among infants born after low risk pregnancy and infants diagnosed with Intra Uterine Growth Restriction (IUGR) Methods: The cross-sectional study included 110 neonates recruited at birth using stratified random sampling based on inclusion and exclusion criteria. Neonates diagnosed without IUGR were allocated to Group I (n = 55) and those diagnosed with IUGR were allocated to Group II (n = 55). Perinatal case history was obtained followed by intraoral examination at birth, 6 months and monthly up to 1 year or till first evidence of teeth eruption. Results: The first evidence of eruption of deciduous teeth was found delayed in Group II (p = 0.0001). The mean gestational age at delivery, estimated fetal weight, frequency of NICU admission, birth weight and infant weight at 6 months was found statistically higher (p = 0.001) in Group I. Conclusion: First evidence of deciduous teeth eruption was found delayed among IUGR infants therefore, IUGR along with prematurity, LBW, LSCS delivery, NICU admission can be considered as risk factor for delayed eruption.